Indications and prescriptions of penicillins in a population of Colombia: A cross-sectional study - Luis Fernando Valladales-Restrepo; Brayan Stiven Aristizábal-Carmona; Luisa María Londoño-Toro; Mariavictoria del Valle Jaramillo-Lima; Mariana Osorno-Ríos; Jorge Enrique Machado-Alba (Brazilian Journal of Infectious Diseases)
Inappropriate use of antibiotics plays a key role in increasing bacterial resistance. The aim was to determine the prescription patterns and approved and unapproved indications for the use of penicillins in a group of patients from Colombia. This was a cross-sectional study on the use of penicillins in outpatients. The subjects were identified from a population-based drug dispensing database. Approved and unapproved indications were determined from records of the Food and Drug Administration (FDA) of the United States and the National Institute of Food and Drug Surveillance (INVIMA) of Colombia. Descriptive and multivariate analyses were performed. A total of 137,070 patients were identified; the average age was 35.8 ± 23.5 years, and 56.2 % were women. Amoxicillin (73.4 %), dicloxacillin (11.7 %) and sultamicillin (6.0 %) were the most prescribed penicillins, mainly for upper respiratory tract infections (43.0 %). In 68.9 % cases, penicillins were used for approved indications, especially to treat Helicobacter pylori (17.3 %). In 31.1 % of cases, penicillin prescriptions were used for unapproved indications (acute rhinopharyngitis: 8.1 %). Patients with skin and soft tissue infections (aOR = 2.82; 95 % CI 2.57‒3.09), with lower respiratory tract infections (aOR = 2.02; 95 % CI 1.89‒2.16), and those treated with dicloxacillin (aOR = 2.84; 95 % CI 2.07‒3.89) were more likely to be prescribed penicillins for unapproved indications. Amoxicillin was the most widely used penicillin in outpatients. Penicillins were frequently used for unapproved indications not recommended by drug regulatory agencies.